MENYOAL EFEKTIVITAS SANKSI PIDANA DALAM TINDAK PIDANA LINGKUNGAN HIDUP DI PROVINSI JAWA BARAT - Ade Mahmud (Law Department Jenderal Achmad Yani University, 2023)
The application of imprisonment for perpetrators of environmental crimes in West Java deserves to be questioned because imprisonment does not show a deterrent effect which affects the reduction of environmental crimes, on that basis the existence of imprisonment should be corrected. This writing aims to explain the effectiveness of imposing sanctions to reduce environmental crimes in West Java Province and to analyze environmental law enforcement to prevent environmental crimes in West Java. This writing method uses a normative legal approach that refers to secondary data in the form of books, journals, research results, regulations and court decisions which are analyzed qualitatively. The effectiveness of criminal sanctions for perpetrators of environmental crimes in West Java has not contributed to reducing environmental crimes, the indicators can be seen from the data of various court decisions in West Java that have imposed prison sentences on perpetrators but reports of environmental cases in West Java have continued to increase. The majority of environmental crimes committed by individuals and corporations aim to gain economic benefits so that environmental law enforcement to prevent environmental crimes is to apply criminal fines to recover losses due to criminal acts and to utilize administrative sanctions, especially government coercion when the business activities carried out cause pollution or damage. quite heavy on the environment so that through administrative legal instruments the government can restore environmental functions